An Analysis of Investment Decisions among Gen Z: Examining the Influence of Risk Perception, Religiosity, and Overconfidence - Tasman, Abel; Lukman, Syukri; Husni, Tafdil; Rahim, Rida; Alfarisi, Mohamad Fany (CV. ITTC INDONESIA, 2024)
The purpose of this research is to analyze the factors that influence the investment decisions of Generation Z in Padang City. Specifically, the study aims to investigate the impact of risk perception, religiosity, and overconfidence on investment decisions. The research method used is causative research, with a sample of 96 respondents from Padang City, who were selected using a purposive sampling method. The data was collected using a questionnaire and analyzed using multiple regression analysis with SPSS. The results of the study indicate that risk perception has a significant positive effect on investment decisions among Generation Z in Padang City. However, the study found no significant positive effect of religiosity or overconfidence on investment decisions